Moonlighters: A Product of Deprivation or Aspiration? - Jamal, Muhammad; Crawford, Ronald (Relations industrielles / Industrial Relations, 1981)
This study explores the nature of relationships between moonlighting and several dependent variables, such as need fulfillment in work and non-work, mental health, participation in voluntary organizations, job performance, absenteeism, anticipated turnover and flex-time and short work week preferences.